Science Edupreneurship Training in Making Kombucha Tea Food Biotechnology Products for Students - Nursamsu, Nursamsu; S. Pandia, Ekariana; Mardiah, Mardiah; Ernawati, Ernawati (Unram Journal of Community Service, 2025)
Activity devotion to public This aiming For increase knowledge and skills participant educate in field biotechnology food through training making kombucha based tea approach science edupreneurship. Training This designed For integrate understanding scientific regarding the fermentation process with strengthening soul entrepreneurship participant educate, especially in utilise potential local as material standard main. The method used covering socialization, demonstration, training practice direct, and evaluation results activities. Evaluation results show that happen improvement significant in aspect understanding the fermentation process, selection material standard, procedure kombucha production, as well as mark nutrition and benefits health products. In addition, training This also provides impact positive in grow interest and motivation participant educate For develop business ideas science based. Activities This expected can become an implementative model in strengthening applied science literacy and skills entrepreneurship for generation young in the economic era creative.